Transplantasi Organ: Tinjauan Moral Bioetika - Priambodo, Leonardus Satrio (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
This paper aims to examine the phenomenon of organ transplantation which is viewed from the perspective of bioethics and Christian moral teachings. Bioethics is part of the study in this paper because nowadays, interdisciplinary and multicultural approaches are increasingly demanded by various parties, including theology. All of these elements are used to see the phenomenon of organ transplantation in a moral bioethical frame. From the research results, the principles of bioethics in the implementation of organ transplantation (the principles of integrity and totality, charity, and informed consent) do not contradict from Christian moral teachings which are based on natural law.